Duplication of the yeast spindle pole body once per cell cycle - Rüthnick, Diana; Schiebel, Elmar (Molecular and cellular biology, 2016)
The yeast spindle pole body (SPB) is the functional equivalent of the mammalian centrosome. Centrosomes and SPBs duplicate exactly once per cell cycle by mechanisms that use the mother structure as a platform for the assembly of the daughter. The conserved Sfi1 and centrin proteins are essential components of the SPB duplication process. Sfi1 is an elongated molecule that has, in its center, 20 to 23 binding sites for the Ca2+-binding protein centrin. In the yeast Saccharomyces cerevisiae, all Sfi1 N termini are in contact with the mother SPB whereas the free C termini are distal to it. During S phase and early mitosis, cyclin-dependent kinase 1 (Cdk1) phosphorylation of mainly serine residues in the Sfi1 C termini blocks the initiation of SPB duplication (“off” state). Upon anaphase onset, the phosphatase Cdc14 dephosphorylates Sfi1 (“on” state) to promote antiparallel and shifted incorporation of cytoplasmic Sfi1 molecules into the half-bridge layer, which thereby elongates into the bridge. The Sfi1 C termini of the two Sfi1 layers localize in the bridge center, whereas the N termini of the newly assembled Sfi1 molecules are distal to the mother SPB. These free Sfi1 N termini then assemble the new SPB in G1 phase. Recruitment of Sfi1 molecules into the anaphase SPB and bridge formation were also observed in Schizosaccharomyces pombe, suggesting that the Sfi1 bridge cycle is conserved between the two organisms. Thus, restricting SPB duplication to one event per cell cycle requires only an oscillation between Cdk1 kinase and Cdc14 phosphatase activities. This clockwork regulates the “on”/“off” state of the Sfi1-centrin receiver.
Gesehen am 07.05.2020